Employee attitudinal and behavioural requirements for entrepreneurial behaviour in South African SMMEs - Ramolobeng, Phuti Zacharia (My University, 2021)
SMMEs are seen, in the context of South Africa, as essential for growing big companies and, by extension, propel the entire economy of the country. This research study’s main focus was on intrapreneurship in South African SMMEs. It explicated the effect that attitude towards intrapreneurship (ATI) and perceived behavioural control (PBC), have on employee intrapreneurial behaviour. It also sought to explain the role played by a firm’s support, as moderator, on the relationships that exist between ATI and PBC, and intrapreneurial behaviour. This study used a quantitative approach, which allows quantification of constructs with scales so that relationships between constructs as well as the strength of such relationships can be tested to accept or reject hypotheses. The study also followed a cross-sectional methodological approach and used online questionnaires to collect primary data from SMME employees in a survey. The target population for the research study comprised employees of SMMEs in South Africa. Some important implications of intrapreneurial behaviour for SMMEs, emanating from the findings would point founders, managers, and employees of SMMEs in the direction of attitudinal and behavioural requirements for intrapreneurial behaviour.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in n Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Corporate entrepreneurship; Firm support; Entrepreneurial orientation; SDG-8: Decent work and economic growth; SDG-8: Decent work and economic growth